Characterization of phage resistance and phages capable of intestinal decolonization of carbapenem-resistant Klebsiella pneumoniae in mice - Fang, Qingqing; Feng, Yu; McNally, Alan; Zong, Zhiyong (Communications biology, 2022)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) has emerged as a severe global health challenge. We isolate and characterize two previously unidentified lytic phages, P24 and P39, with large burst sizes active against ST11 KL64, a major CRKP lineage. P24 and P39 represent species of the genera Przondovirus ( Studiervirinae subfamily) and Webervirus ( Drexlerviridae family), respectively. P24 and P39 together restrain CRKP growth to nearly 8 h. Phage-resistant mutants exhibit reduced capsule production and decreased virulence. Modifications in mshA and wcaJ encoding capsule polysaccharide synthesis mediate P24 resistance whilst mutations in epsJ encoding exopolysaccharide synthesis cause P39 resistance. We test P24 alone and together with P39 for decolonizing CRKP using mouse intestinal colonization models. Bacterial load shed decrease significantly in mice treated with P24 and P39. In conclusion, we report the characterization of two previously unidentified lytic phages against CRKP, revealing phage resistance mechanisms and demonstrating the potential of lytic phages for intestinal decolonization. Fang et al. characterized two previously unidentified phage species that could inhibit growth and decrease virulence of carbapenem-resistant Klebsiella pneumoniae (CRKP). They also showed that CRKP develop phage resistance but could still be decolonized in a mouse intestinal colonization model, highlighting phage therapy as potential treatment against drug-resistant pathogens.